أثر الاستثمار في رأس المال البشري على النمو الاقتصادي في الجمهورية العربية السورية - حيدر, عز الدين; إبراهيم, عمار (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aims to study the impact of investment in human capital for economic growth in Syria during the period between 2000 and 2010 using a form Kub- Douglas and neoclassical growth models, correlation and analysis of variance for data processing in order to build three basic models. The first model is designed to measure the impact of the workforce on the GDP growth rate of the growth rate, while the second model aims to measure the impact of the growth of the number of students enrolled in various educational stages of the GDP growth rate, and the third model is designed to measure the impact of the proportion of education budget balancing public on the GDP growth rate. The researcher concluded that there is the effect of a statistically significant rate of growth of the operational category and the rate of physical capital growth on the GDP growth rate in Syria, the growth of the overall operational category him rate the impact of higher gross fixed capital formation growth rate of the GDP rate, and that There is a statistically significant effect of the ratio of education budget on the GDP growth rate in Syria, but no statistically significant effect of the rate of growth in the number of students enrolled in the various stages of education on the GDP growth rate in Syria يهدف البحث إلى دراسة أثر الاستثمار في رأس المال البشري على النمو الاقتصادي في سورية خلال الفترة الواقعة بين عامي 2000 و2010 باستخدام نموذج كوب- دوغلاس ونماذج النمو النيوكلاسيكي, والارتباط وتحليل التباين لمعالجة البيانات بهدف بناء ثلاث نماذج أساسية. يهدف النموذج الأول إلى قياس أثر معدل نمو القوى العاملة على معدل نمو الناتج المحلي الإجمالي, أما النموذج الثاني فيهدف إلى قياس أثر نمو عدد الطلاب المسجلين في مراحل التعليمية المختلفة على معدل نمو الناتج المحلي الإجمالي, والنموذج الثالث يهدف إلى قياس أثر نسبة موازنة التعليم من الموازنة العامة على معدل نمو الناتج المحلي الإجمالي. وتوصل الباحث إلى أنه يوجد أثر ذو دلالة احصائية لمعدل نمو الفئة التشغيلية ومعدل نمو رأس المال المادي على معدل نمو الناتج المحلي الإجمالي في سورية, كما أن معدل نمو الفئة التشغيلية الكلية له أثر أعلى من معدل نمو تكوين رأس المال الثابت الإجمالي على معدل الناتج المحلي الإجمالي, وأنه يوجد أثر ذو دلالة احصائية لنسبة موازنة التعليم من الموازنة العامة على معدل نمو الناتج المحلي الإجمالي السوري, ولكن لا يوجد أثر ذو دلالة احصائية لمعدل نمو عدد الطلاب المسجلين في المراحل التعليمية المختلفة على معدل نمو الناتج المحلي الإجمالي السوري.